Self-Communicating Deep Reinforcement Learning Agents Develop External Number Representations - Sabathiel, Silvester; Solstad, Trygve; Testolin, Alberto; Petruzzellis, Flavio (Proceedings of the Northern Lights Deep Learning Workshop, 2022)
Symbolic numbers are a remarkable product of human cultural development. The developmental process involved the creation and progressive refinement of material representational tools, such as notched tallies, knotted strings, and counting boards. In this paper, we introduce a computational framework that allows the investigation of how material representations might support number processing in a deep reinforcement learning scenario. In this framework, agents can use an external, discrete state to communicate information to solve a simple numerical estimation task. We find that different perceptual and processing constraints result in different emergent representations, whose specific characteristics can facilitate the learning and communication of numbers.